2014
DOI: 10.1111/jvh.12359
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the free‐vaccine policy on timely initiation and completion of hepatitis B vaccination in Fujian, China

Abstract: The extent to which the free-vaccine policy impacts the initiation and completion of a hepatitis B vaccine series is poorly understood. The aim of this study was to evaluate the impact of the free-vaccine policy on hepatitis B vaccination. A provincial survey was conducted in 2006 in Fujian Province, south-east of China, where the free-vaccine policy for hepatitis B was announced in 2002 and implemented in 2003. A total of 1628 children were investigated, and 1443 (88.6%) were included in this analysis. Among … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 20 publications
3
23
1
Order By: Relevance
“…Although there had been a great improvement in infant Hep B coverage, this study showed that certain groups remained at high risk of not receiving a timely birth dose or full immunization. This was consistent with previous reports from other provinces of China [4,14,15,16,17], and was attributed to risk factors such as uneven economic development, rural areas, and ethnic minorities. Other reports from some developing countries attributed the delayed or incomplete Hep B vaccination to the poor practice of the vaccination service [18,19,20].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Although there had been a great improvement in infant Hep B coverage, this study showed that certain groups remained at high risk of not receiving a timely birth dose or full immunization. This was consistent with previous reports from other provinces of China [4,14,15,16,17], and was attributed to risk factors such as uneven economic development, rural areas, and ethnic minorities. Other reports from some developing countries attributed the delayed or incomplete Hep B vaccination to the poor practice of the vaccination service [18,19,20].…”
Section: Discussionsupporting
confidence: 93%
“…The recommended schedule involves the administration of Hep B1 within 24 h after birth and the administration of two subsequent doses at 1 and 6 months of age. This scheme can not only effectively prevent mother-to-child transmission, but also provide lifelong protection [4].…”
Section: Introductionmentioning
confidence: 99%
“…Minority children were less likely to complete the EPI, which may be related to poor economic conditions of their families 34 and the lack of vaccination awareness of their parents. 35 Similar to previous studies, 36 37 we confirmed that timely HepB first dose initiation improved the EPI completion in children, possibly because receiving a timely HepB first dose might help emphasise the importance of vaccination to the parents and promote their children’ completion of the EPI. 1 …”
Section: Discussionsupporting
confidence: 85%
“…The prevalence of positivity for hepatitis B surface antigen was estimated to be 10.2% in the population aged 1 to 59 years in 2006. 1 To control HBV infection, hepatitis B vaccine (HB vaccine) has been recommended for newborns and infants since 1992, and was included in the national immunization program vaccine (NIPV) series in 2002. 2 It is recommended that infants receive three doses of HB vaccine, to be given within 24 h after birth and at 1 month and 6 months of age.…”
mentioning
confidence: 99%